A new methodology to predict damage tolerance based on compliance via global-local analysis (Fracture and Structural Integrity, 2021)
Over the years several design philosophies to fatigue developed in order to combine structural safety and economy to manufacturing and operating aircraft process. The safe-life approach, which consists of designing and manufacturing a safe aeronautical structure throughout its useful life, results in factors that oversize the structural elements, preventing the possibility of failure and evidently leading to high design costs. On the other hand, the approach based on the damage tolerance concept, in which it is assumed that the structure, even whether damaged, is able to withstand the actions for which it was designed until the detection of a crack due to fatigue or other defects during its operation. Here, we propose a new methodology to the damage tolerance problem in which two-dimensional global-local analysis at different levels of external requests will be made by means of compliance, aimed at finding a relationship between fatigue life and the Paris constant. Moreover, the BemCracker2D program for simulating two-dimensional crack growth is used. This methodology has been proved to be an efficient and applied alternative in the damage tolerance analysis.
Keywords: Compliance; Damage tolerance; Fatigue; Global-local analysis; Aircraft fuselage; BEM